Brokering in Education Research-Practice Partnerships A Guide for Education Professionals and Researchers - Wentworth, Laura (Taylor & Francis, 2023)
Educational leaders, researchers, and community members have found collaborating on research supports improvement in their schools, districts, and the wider community - but how do we go about developing these partnerships? With essential tools, frameworks, and tips for brokering in research-practice partnerships (RPPs), this practical book provides guidance on cultivating and sustaining impactful relationships and supportive infrastructure with partners. Through the careful brokering of these partnerships, RPP brokers can bridge the gap between education research and practice, bringing people together to build a more equitable educational system. Written by RPP leaders, researchers, and professionals, this handbook explores how brokering can: Support the production and use of partnership research Develop and nurture meaningful relationships, even in the face of challenging circumstances Build individual competencies to manage an RPP and strengthen the partnership Develop partnership governance Implement effective administrative structures Design processes and communications routines Assess and continuously improve the partnership This is an essential read for any educational leader, higher education faculty, researcher, or other community member who wants to understand the types of activities and responsibilities required of an RPP broker and the strategies to become an effective broker of RPPs aimed at educational improvement and equitable transformation.